ANALISIS SEMIOTIKA FILM CHRISTIAN METZ: STUDI KASUS VISUALISASI PESAN RELIGI DALAM FILM HIJRAH CINTA - Alga Lilis Kusuma Dewi; Muhammad Zamroni; Soekma Yeni Astuti (Publika Budaya, 2017)
AbstractThis study was investigating about religion message visualization in film “Hijrah Cinta”. The goal of this study was to know about religion message visualization and it purposed in film “Hijrah Cinta”. This study used the descriptive-qualitiative method which explained the detail of the problem showed on this study. The data analysis in the object used the semiotics analiysis technic. The concept which used in this study was : religion message concept, then the theory whisch used was film semiotics Christian Metz theory and Gestalt cognitive psycology theory. The data analysis result shown the conclusion that the religion message in “Hijrah Cinta” shot series was sincere, patient, no surrender and godfearing. Those message was described to 7 syntagmas by Metz. The explanation of religion message was more complete with presence of gestalt psychological based analysis. 5 characteristic of insight in learning formed the comprehension about sincere, godfearing on religious proselytizing.